“FORMULATING JOKOTOLE’S HERO'S JOURNEY: ANALYSIS OF THE LIFE JOURNEY OF THE MADURA’S LEGEND" - Ahmad, Ahmad; Inayati, Rif'ah; Hartanto, Erika Citra Sari (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2024)
This study looks at Madura's culture using Joseph Campbell's Hero's Journey, focusing on the story of Jokotole. It explores how this tale shares regular story parts and reflects Madura's culture using Campbell's ideas. The different parts of the Hero's Journey, like 'Call to Adventure' and 'Tests, Allies, and Enemies,' show how Jokotole changes during the story. This study shows how the story is lasting, teaches good values, and tells about Madura's way of life. It's not just a story; it keeps important things about who Madura's people are and what they believe. This research shows that Madura's stories are still important today, crossing time and cultures. It helps us see how stories connect people all around the world. Keywords: Madurese legends, Hero's Journey, Cultural insights.